Discovery of potent, selective small molecule inhibitors of α-subtype of type III phosphatidylinositol-4-kinase (PI4KIIIα). Issue 16 (15th August 2015) - Raubo, Piotr; Andrews, David M.; McKelvie, Jennifer C.; Robb, Graeme R.; Smith, James M.; Swarbrick, Martin E.; Waring, Michael J.
Graphical abstract: Abstract: The discovery and optimisation of novel, potent and selective small molecule inhibitors of the α-isoform of type III phosphatidylinositol-4-kinase (PI4Kα) are described. Lead compounds show cellular activity consistent with their PI4Kα potency inhibiting the accumulation of IP1 after PDGF stimulation and reducing cellular PIP, PIP2 and PIP3 levels. Hence, these compounds are useful in vitro tools to delineate the complex biological pathways involved in signalling through PI4Kα.